Gambaran Pengetahuan dan Sikap Warga Tentang Manajemen Pra Bencana Banjir di Kelurahan Bugel Kecamatan Polokarto - Anisa Ismawanti; Hermawati Hermawati (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Bugel Village is one of the villages in Polokarto Sub-district that is often affected by natural disasters in the form of floods because of its location in the lowlands close to the Bengawan Solo River tributaries, namely the Langsur and Samin River. When there is high rainfall, the Bengawan Solo River experiences an increase in water discharge so that water from tributaries cannot enter the Bengawan Solo River and damage the embankment and river siltation caused by garbage. to determine the description of residents' knowledge and attitudes about pre-disaster flood management in Bugel Village, Polokarto Subdistrict. This type of research uses descriptive methods with a quantitative approach, with a population of 477 people sampling 83 respondents. The research instrument used a questionnaire with data analysis using univariate analysis. The results of the majority of knowledge research in the good category as many as 79 (95.2%) respondents and 4 (4.8%) respondents in the sufficient category. Then the results of attitude research in the moderate category were 46 (55,4%) respondents and 37 (44,6%) in the good category. The knowledge of residents in RW 6 Bugel Village, Polokarto Subdistrict is in the good category, while the attitudes of residents are in the moderate category.